2008
DOI: 10.1038/bjp.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

The new water‐soluble artemisinin derivative SM905 ameliorates collagen‐induced arthritis by suppression of inflammatory and Th17 responses

Abstract: Background and purpose: Our previous study showed that SM905, a novel artemisinin derivative, exhibited potent immunosuppressive activity. In this study, we evaluate preventive and therapeutic effect of SM905 on collagen-induced arthritis (CIA) in DBA/1 mice, and investigate its mechanisms both in inflammatory and autoimmune aspects of the disease. Experimental approach: CIA was induced by type II bovine collagen (CII) in DBA/1 mice. SM905 was given orally either before (continuously 1 day before booster immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…81 The results of this study supported the view that amelioration of CIA could be accomplished only by reducing the levels of both Th17 and IL-6.…”
Section: Potential Novel Mechanisms Revealed For the Role Of Il-6 In supporting
confidence: 79%
“…81 The results of this study supported the view that amelioration of CIA could be accomplished only by reducing the levels of both Th17 and IL-6.…”
Section: Potential Novel Mechanisms Revealed For the Role Of Il-6 In supporting
confidence: 79%
“…In contrast, in vivo SM934 could significantly suppress the Th1-mediated delayed-type hypersensitivity reaction even at a dosage of 1 mg/kg/day (27). Moreover, our previous studies demonstrated that artemisinin derivatives possessed therapeutic effects on collagen-induced arthritis by suppressing pathogenic Th17 cell responses (26).…”
mentioning
confidence: 93%
“…However, most artemisinin derivatives possess poor water solubility or low bioavailability, which limits their further applications to treat autoimmune diseases. Several series of new artemisinin derivatives have been synthesized, and the water-soluble artemisinin derivative SM934 showed higher bioavailability, better bioactivity, and lower toxicity (25)(26)(27)(28). The acute toxicity of SM934 was tested in mice, and the median lethal dose was ϳ2 gm/kg.…”
mentioning
confidence: 99%
“…At last, SM 735, SM 905, SM 933, and SM 934 ( Figure 2) were selected and tested in the animal models for 2,4-dinitrofluorobenzene (DNFB)-induced delayed-type hypersensitivity (DTH) reaction, sheep red blood cell (SRBC)-induced antibody production, and experimental autoimmune encephalomyelitis (EAE). Up to date, a number of papers related their immuno-suppressive activity and possible mechanisms have been published mainly from this Institute [55][56][57][58][59][60][61][62][63][64] . The preclinical research of SM 934 is in progress.…”
mentioning
confidence: 99%